Optimal control of hydrosystems - Mays, Larry W. (Marcel Dekker, 1997)
Combines the hydraulic simulation of physical processes with mathematical programming and differential dynamic programming techniques to ensure the optimization of hydrosystems. Presents the principles and methodologies for systems and optimal control concepts; features differential dynamic programming in developing models and solution algorithms for groundwater, real-time flood and sediment control of river-reservoir systems, and water distribution systems operations, as well as bay and estuary freshwater inflow reservoir oprations; and more.